A novel watermarking technique in data transmission between QR codes and database - Mohamed, Kartini; Sidi, Fatimah; A. Jabar, Marzanah; Ishak, Iskandar (IEEE (IEEEXplore), 2013)
Digital data transmission has become prominent in this era of communication. Digital data such as text, still images, movies, or sounds can be wirelessly distributed through internet, intranet or digital broadcasting. A recent data management technology known as QR Code (Quick Response Code) allows data or information to be communicated wirelessly using a common portable device installed with its scanning software. Even though this new data management technology is easy to handle, it is also easy to be duplicated by unauthorized parties. Besides authentication and encryption techniques for security, using watermark will be an advantage to provide better protections for wireless data transmissions. This paper describes how these protections are being applied in ensuring data transmission for QR Codes safe from intruders without affecting the quality of data transmitted. A different technique of applying watermark is proposed in this paper. In this technique, due to its unique information, data of authentication is used for the watermark. The technique is also supported with the use of binary numbers for the encryption. To confirm the effectiveness of this protection technique, percentage of data loss and processing time for data transmissions are measured. From the experiment, results show that there is no data loss but only a slight delay in processing time is observed. This shows that the proposed technique of security protection is effective with only a negligible amount of time delay.